Adverse Events Related to Kratom Discontinuation and the Utilization of Prescribed Medications During Hospitalization: A 4-year Retrospective Study in Thanyarak Songkhla Hospital, Thailand - Sitaruno, Sirima; Wungsintaweekul, Juraithip; Wanishayakorn, Tanatape; Kanjanasintou, Tharin; Srisai, Nattrawee; Kongruen, Chanocknun; Chaimongkon, Chawisa; Sodadis, Saodaro; Putthachat, Thanurat (Journal of Health Science and Medical Research, 2024)
Objective: The purpose of this study was to investigate adverse events related to kratom cessation and the utilization of prescribed medications during hospitalization. Material and Methods: This retrospective study was conducted in Thanyarak Songkhla Hospital, Thailand. The study included patients aged 15 years and above who had a history of kratom consumption prior to hospitalization. Adverse events after kratom discontinuation during the patient’s hospital admission were documented. The prescribed drug regimens during hospitalization were recorded. Results: During the 4-year study period, 81 patients were enrolled. Fifty-four patients (67%) developed adverse events. The majority of enrolled patients were males between the ages of 15 and 34 years. The popular 4x100 kratom cocktail was commonly consumed prior to admission. Musculoskeletal pain (28%) and psychological disorders such as insomnia, agitation, and anxiety were observed as major adverse events. Patients with adverse events received more medications than those without adverse events (p-value=0.02). Typical antipsychotics were commonly prescribed for patients with adverse events related to kratom discontinuation (p-value<0.01). Conclusion: In hospitalized patients who had consumed kratom previously, 67% experienced adverse events. The most common adverse events were musculoskeletal pain and psychological disorders. In patients with adverse events, antipsychotics were commonly prescribed. A history of kratom consumption should be asked during hospitalization for all admitted patients to assess the possibility of an adverse event and provide appropriate management.